MALDI-TOF MS as a method for rapid identification of Phytophthora de Bary, 1876 - Božik, Matěj; Mrázková, Marcela; Novotná, Karolína; Hrabětová, Markéta; Maršik, Petr; Klouček, Pavel; Černý, Karel (PeerJ, 2021)
The number of described species of the oomycete genus Phytophthora is growing rapidly, highlighting the need for low-cost, rapid tools for species identification. Here, a collection of 24 Phytophthora species (42 samples) from natural as well as anthropogenic habitats were genetically identified using the internal transcribed spacer (ITS) and cytochrome c oxidase subunit I (COI) regions. Because genetic identification is time consuming, we have created a complementary method based on by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). Both methods were compared and hypothesis that the MALDI-TOF MS method can be a fast and reliable method for the identification of oomycetes was confirmed. Over 3500 mass spectra were acquired, manually reviewed for quality control, and consolidated into a single reference library using the Bruker MALDI Biotyper platform. Finally, a database containing 144 main spectra (MSPs) was created and published in repository. The method presented in this study will facilitate the use of MALDI-TOF MS as a complement to existing approaches for fast, reliable identification of Phytophthora isolates.
Keywords: COI; Protein; Library; Mass spectra; Species determination; Maldi; Database; ITS; Phytophthora; Biotyping